Effects of sleep quality on the work performance of taxi drivers - Bustilo, Clyde Jason; Gonzales, Paolo; Pilla, Kent; Prado, Rom John; Ramos, Christie Lou; Tay Mikee
This study aimed to investigate whether sleep quality affects the work performance of taxi drivers. Socio-demographic factors were also studied in order to know whether or not they affect the sleep quality of the taxi drivers. The Light of Glory Taxi Services Company was chosen to be the subject of this research. In order to gain knowledge about the work shift schedule of the taxi drivers, an interview with the management was conducted. The formal survey was then carried out from April 3 to April 7, 2017 with a total of 55 taxi drivers as respondents. Sleep quality was measured and evaluated using the Pittsburgh Sleep Quality Index (PSQI). The work performance indicators chosen were the weekly revenues earned, number of bump-outs and traffic violations committed, number of absences incurred and the occurrence of tardiness for the previous month. Socio-demographic factors included were age, no years working as taxi driver and no. years assigned in the current shift. The results of the survey showed that majority of the drivers from all shifts suffered from poor sleep quality (global PSQI ≥5) (10 PM : 54%, Straight Duty : 56%, 24 hours : 80%). Performance of Good Sleepers (GS) and Poor Sleepers (PS) were also compared. For the 10 PM and straight duty shift schedule, there were no significant difference in the performance between GS and PS. However, for drivers in the 24-hour shift schedule, PS incurred higher absences on the average compared to the GS. Interestingly, PS also earned higher revenues compared to the GS on this shift. Spearman's rank correlation test was also performed to determine the relationship of various sleep quality factors with the performance indicators. The results of the test revealed that impairment in the sleep quality of the taxi drivers would generally result to the impairment of their work performance as well. However, the outcomes vary on the three shifts regarding the relationship of sleep quality factors and the work performance indicators affected. For the socio-demographic factors, each shift was also affected differently. The 10-pm shifter's sleep quality is mainly affected by the number of years spent in the shift, while on the straight duty, it is the number of years working as a taxi driver that affects their sleep quality. On the other hand, no correlation was found between the PSQI scores of the 24-hour shifters and their socio-demographic factors. The results of the study would justify a management mandate to improve the scheduling of its existing shifts, especially for the 24-hour schedule. In order to help the drivers obtain an adequate amount of sleep. Additionally, the researchers also suggest that management conduct more informative seminars to inform the drivers of the possible detrimental effects of having poor sleep quality on their mental and cognitive abilities, swell as their motivation in work. In this way, the taxi drivers may be encouraged to manage their time effectively and make efforts to improve their sleep quality, which in turn helps them on improving their workweek performance as well.